(3GdeQTO aj GdJMdjd GdEMUGFj ddHjGfGJ HGSJNOGe (BSPSSs - (3LeGd eMeO TGcQ(B, (3eMeOs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2005)
(3ebOeI aj Yde GdEMUGA(B- (3GdHQfGeL GdEMUGFj (BSPSS- (3GdeYGdLI GdafjI ddHjGfGJ(B- (3GdJMdjd GdEMUGFj GdhUaj ddeJZjQGJ GdfhYjI(B- (3GdJMdjd GdEMUGFj GdhUaj ddeJZjQGJ GdcejI(B- (3GdJMdjd GdEMUGFj dCcKQ ef eJZjQs
(3GdeQGLY U(B.324s
Keywords: SPSS; (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdJMdjd GdEMUGFj(B- (3JNRjf hGSJQLGY GdeYdheGJs